2011
DOI: 10.1179/2045772311y.0000000032
|View full text |Cite
|
Sign up to set email alerts
|

An effective oral vitamin D replacement therapy in persons with spinal cord injury

Abstract: Background/objective: Vitamin D deficiency is prevalent in chronic spinal cord injury (SCI). A 3-month course of oral vitamin D 3 to 'normalize' serum vitamin D levels was investigated. Design: Prospective drug-intervention study. Setting: VA Medical Center; private rehabilitation facility. Methods: Seven individuals with chronic SCI and vitamin D deficiency completed 3 months of oral vitamin D 3 (i.e. cholecalciferol) supplementation. At screening, baseline, and months 1 and 3, blood was collected for serum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…It's important to emphasize that this study was performed in a subtropical region, what could contribute with the low vitamin D levels. This finding is similar to the data published by Bauman et al [17] that also evaluated subjects with SCI. These authors detected a mean concentration of vitamin D of 14 ng/mL in the assessed group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It's important to emphasize that this study was performed in a subtropical region, what could contribute with the low vitamin D levels. This finding is similar to the data published by Bauman et al [17] that also evaluated subjects with SCI. These authors detected a mean concentration of vitamin D of 14 ng/mL in the assessed group.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is probably related to the shorter time of sun exposure due to limited mobility. SCI is a complex condition that leads to biopsychosocial and lifestyle changes [15,17]. This low solar exposure in patients with SCI could be related with longstanding hospitalization, immobilization, as well as the lack of financial conditions, which entails the impossibility of hiring a professional who could assist the patient's locomotion, in order to increase the time of sun exposition [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few other studies investigated the effect of vitamin D supplementation on vitamin D status in individuals with a spinal cord injury [27,38,39]. Most of these studies failed to achieve a sufficient vitamin D status after the supplementation period [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of patients in rehabilitation to go outdoors and obtain vitamin D from sun exposure is often limited due to decreased functional mobility and hospitalization . In looking toward decreasing these risks, previous studies demonstrated that vitamin D supplementation reduced the rate of vitamin D deficiency in patients undergoing rehabiliation . Despite the evidence of widespread VDD and VDI in rehabilitation patients and the effectiveness of vitamin D supplementation in increasing serum levels, there is limited literature regarding effective interventions to increase screening and supplementation in the acute inpatient rehabilitation setting.…”
Section: Introductionmentioning
confidence: 99%